Kaj moramo vedeti o zdravniški poklicni etiki pri delu z ljudmi - Iljaž, Rade (Medicinski razgledi, 2004)
Teaching about medical ethics and deontology, included in curriculums of most important medical faculties in Europe and USA, has a long and successful tradition in Slovenia too. Considering that we are living in the age of new technologies, globalization and expeditious development in every branch of knowledge, modern physician is continuously confronted with new professional challenges and ethical puzzles. Trying to solve ethical dilemmas, we are obliged to respect our professional ethical codes and basic ethical principlesof medical profession such as beneficence, truthtelling, non-maleficence, patient's autonomy, justice and confidentiality. Ethical problems arise above all when we are breaking some of these basic ethical rules from different reasons. Ethical problems are frequently overlooked. By performing good medical practice, keeping our medical knowledge up-to date andpermanently considering valid legal regulations, we gain the powerful toolsfor solving ethical dilemmas and for our professional promotion at the same time. Confronted with more difficult ethical problems, we are obliged to consult more experienced colleagues or professional and ethical boards.
Keywords: Ethics, Professional; Etika medicinska; Etika poklicna; Ethics, Medical; Zdravnik-bolnik, odnosi; Physician-Patient Relations; poklicna etika; medicinska etika